Crosstalk error analysis in IIDFC readout circuit for use in piezoresistive composite - Castro, Fabian [UNESP]; Pentiado, Thiago [UNESP]; Blanco, Jorge [UNESP]; Xavier, Ricardo [UNESP]; Sanches, Marcelo [UNESP]; De Carvalho, Aparecido [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Resistive sensor arrays (RSAs) have been developed for a variety of applications depending on resolution requirements, active sensor area, and cost. Composite-based piezoresistive sensors are commonly found in RSAs. However, they present an intrinsic problem related to the parasitic current paths that flow through the whole composite, which cause a crosstalk effect. Various circuits have been proposed to reduce the crosstalk effect in sensor arrays. In this paper, we compare a number of readout circuits with PSpice models, mainly those including voltage feedback (VF) circuits and zero potential (ZP) circuits. To develop an array with 3600 sensors using a piezoresistive composite, we selected the improved isolated drive feedback circuit (IIDFC). Using nodal analysis, we were able to develop an alternative mathematical circuit model, which allowed us to identify its unique characteristics, including the influence of array size on the crosstalk effect and the restriction on minimal impedance that the array elements must attain to maintain a minimum error. In a resistive array with 3600 sensors and a sensor range of 10-100 kω, we obtained an absolute error of less than 3.56%. In addition, the proposed mathematical circuit model obtained a maximum absolute error difference of 0.03% when compared with the PSpice model with the precision operational amplifier OPA37. Thus, using the IIDFC circuit and considering the minimal allowable impedance, it is possible to maintain a reduced error in an RSA with a large number of sensors.
Keywords: Crosstalk effect; Improved isolated drive feedback circuit; Minimal allowable impedance; Piezoresistive composite; Resistive sensor array